Às margens do rio: analisando o processo de licenciamento ambiental para a mineração de areia na Paraíba - Souza, Renata Gonçalves de (2022)
This research’s problematic is understanding how the environmental licensing on sand extraction works in the state of Paraiba, having as the main question the answer to the following question: “Is SUDEMA processing the environmental licensing of the sand without the due observance of resolution #10 of CONAMA and IBAMA’s normative instruction #4?”. In order to answer that question, the following hypothesis was made: “the Superintendency of Environmental Administration of Paraíba (SUDEMA) would be issuing environmental licenses without the presence of the technical environmental instruments RIMA, EIA/RIMA, RCA, PCA and without the due requirement of PRAD”. In terms of the general objective, it is: “to analyse, through a case study carried out in the environmental licensing processes for sand extraction, if SUDEMA is acting in accordance with the resolution #10 of CONAMA and IBAMA’s normative instruction #4, when authorizing the release of environmental licenses that deal with the extraction of sand from the riverbed”. In order for this objective to be achieved, the deductive method of approach was used, starting from a general analysis of the topic to an analysis of a particular case. Regarding the methodology, literature, bibliographic and documentary reviews were used. In an attempt to provide the theoretical basis on the subject, the descriptive analytical procedure method was used, thus carrying out a theoretical reflection on the environmental issue, on the environmental licensing processes, environmental licensing of mineral aggregates for direct implementation in civil construction, especially sand extraction so that they can base the discussion on the answers obtained through the questionnaire that was used to extract the necessary information from the five environmental licensing processes that provided the data to answer to the hypothesis created. Finally, the Dissertation is divided into five parts, namely: the first consists of the introduction, the second part that addresses the history and importance of mining and sand for society, the third which explains the environmental licensing for mineral aggregates, especially sand, the fourth part that brings the case study, which consists of the analysis of environmental licensing processes and the final part that brings final considerations.